1998
DOI: 10.1159/000007480
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Recurrence of Colorectal Polyps: A Double-Blind 3-Year Intervention with Calcium and Antioxidants

Abstract: Background: Dietary calcium and antioxidants have been suggested as protective agents against colorectal cancer. This has been supported by animal experimental studies, case control and cohort studies. Materials and Methods: In a prospective intervention study of colorectal adenomas, and intermediary stage in colorectal carcinogenesis, 116 polyp-bearing patients received a placebo-controlled daily mixture of β-carotene 15 mg, vitamin C 150 mg, vitamin E 75 mg, selenium 101 µg, and calcium (1.6 g daily) as carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 45 publications
2
107
1
2
Order By: Relevance
“…Any dropouts from the intervention study (Hofstad et al, 1998) was to be avoided. Weighing of foods and drinks is a demanding task, and we did not want to jeopardise the compliance of the 116 polyp patients by asking them all to perform a repeated 5 day food record by weighing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Any dropouts from the intervention study (Hofstad et al, 1998) was to be avoided. Weighing of foods and drinks is a demanding task, and we did not want to jeopardise the compliance of the 116 polyp patients by asking them all to perform a repeated 5 day food record by weighing.…”
Section: Discussionmentioning
confidence: 99%
“…All 116 polyp-bearing out-patients (50% men), aged 50 ± 76 y, who participated in a double-blind 3 y placebocontrolled intervention study against growth and recurrence of polyps (Hofstad et al, 1992(Hofstad et al, , 1998, performed a 5 day dietary record by weighing at inclusion. A subsample of 30 polyp patients was asked to perform a second 5 day dietary record by weighing after 1 y of intervention.…”
Section: Subjects and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Case-control and prospective epidemiological studies show moderate inverse association (a decrease around 25%) between calcium intake and CRC risk (60,61). There are also interesting data from randomized clinical trials that show that calcium supplementation (1,200-2,000 mg per day) produces a modest, but rapid decrease in the incidence of recurrent colorectal adenomas (62)(63)(64)(65)(66), although in one of the studies (66) such an effect was only observed in subjects with higher levels of vitamin D, suggesting that perhaps both calcium and adequate levels of vitamin D are required for the protective effect to be exerted. Different mechanisms have been proposed for calcium's potential to reduce the risk of colorectal cancer: from binding secondary bile acids and fatty acids, sequestering these mutagenic substances from contact with epithelial cells, to a direct action decreasing colonic epithelial cell proliferation and promoting its differentiation, through a calcium-sensing receptor (67)(68)(69).…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%